Predictors of blood ionized calcium concentration in sick adult cattle - Karapinar, Tolga; Tumer, Kenan Cagri; Constable, Peter D.; Buczinski, Sebastien M. C. (Wiley, 2024)
BackgroundData on the factors affecting blood ionized calcium concentration (ciCa2+) and diagnostic performance of serum total calcium concentration (ctCa) measurements to detect abnormal blood iCa2+ status are lacking in sick adult cattle.ObjectiveAssess the association of ciCa2+ with venous blood pH, plasma concentrations of chloride (cCl), sodium (cNa), and potassium (cK), and ctCa, and total protein, albumin, and globulin concentrations in sick adult cattle.AnimalsTwo-hundred and sixty-five adult cattle (>= 1-year-old) with different diseases.MethodsProspective study. Whole blood pH, ciCa2+, cNa, cK, and cCl were measured using a blood gas and electrolyte analyzer, whereas ctCa, and total protein, and albumin concentrations were determined using an autoanalyzer. The relationship between ciCa2+ and venous blood pH, plasma cCl, cNa, cK, and ctCa, and total protein, albumin, and globulin concentrations was investigated. Sensitivity and specificity were calculated for ctCa for diagnosis of abnormal ciCa2+.ResultsSensitivity of ctCa measurements to detect abnormal ciCa2+ was 66.0% whereas specificity of ctCa measurements was 72.3%. Serum total calcium concentration measurements accounted for 42% of adjusted blood ionized calcium (iCa2+7.40) concentration variance. Plasma cCl, and cK had explanatory power of ciCa2+7.40, accounting for an additional 21% and 9% of the variance, respectively.Conclusions and Clinical ImportanceSerum tCa measurements failed to accurately predict blood iCa2+ status in ill adult cattle. Serum tCa concentrations and plasma cCl were the strongest predictors of ciCa2+ in sick adult cattle.
Keywords: blood pH; hypochloremia; ionized calcium